2008
DOI: 10.1016/j.acn.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Detecting malingering in traumatic brain injury and chronic pain with an abbreviated version of the Meyers Index for the MMPI-2

Abstract: Meyers, Millis, and Volkert [Meyers, J. E., Millis, S. R., & Volkert, K. (2002). A validity index for the MMPI-2. Archives of Clinical Neuropsychology, 17, 157-169] developed a method to detect malingering in chronic pain patients using seven scales from the Minnesota Multiphasic Inventory-2 (MMPI-2). This method may be impractical because two of the scales (Obvious minus Subtle and Dissimulation-revised) are not reported by the commercially available Pearson computerized scoring system. The current study reca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…In its initial validation study, it demonstrated a strong ability to differentiate between chronic pain patients in litigation, compared to non-litigating chronic pain patients, with a specificity of 1.0 and sensitivity of .86. These results were replicated in an independent study involving chronic pain patients, with similar results observed (Bianchini et al, 2008), and this index's functioning was also examined in TBI patients in two different studies and demonstrated good ability to differentiate between TBI patients under litigation; however, classification accuracy was not as high as with chronic pain patients (Aguerrevere, Greve, Bianchini, & Meyers, 2008;Dionysus, Denney, & Halfaker, 2011;. These finding are expected, given the fact this index was created using chronic pain patients.…”
Section: Henry-heilbronner Index (Hhi)supporting
confidence: 59%
“…In its initial validation study, it demonstrated a strong ability to differentiate between chronic pain patients in litigation, compared to non-litigating chronic pain patients, with a specificity of 1.0 and sensitivity of .86. These results were replicated in an independent study involving chronic pain patients, with similar results observed (Bianchini et al, 2008), and this index's functioning was also examined in TBI patients in two different studies and demonstrated good ability to differentiate between TBI patients under litigation; however, classification accuracy was not as high as with chronic pain patients (Aguerrevere, Greve, Bianchini, & Meyers, 2008;Dionysus, Denney, & Halfaker, 2011;. These finding are expected, given the fact this index was created using chronic pain patients.…”
Section: Henry-heilbronner Index (Hhi)supporting
confidence: 59%
“…a Findings from the Bianchini and Greve research program often do not specify (a) the source of the data or (b) the overlap, if any, between reported studies. For this table, we excluded any study that explicitly acknowledged their sample as being previously reported upon in published literature (see Aguerrevere, Greve, Bianchini, & Meyers, 2008), but included those in which subject overlap appeared likely (i.e., [17] [19]). b…”
Section: Malingering Research With Mnd Criteriamentioning
confidence: 99%
“…Since the perception of pain is purely subjective, physical tests play a limited role in the differential assessment of malingering; therefore psychological assessment is a good, even indispensable, complement for differential diagnosis. Although instruments have been developed for this purpose, some of them exclusively, such as TOMM, MMPI is the benchmark instrument in psychological assessment and the assessment of malingering (Greene, 2011;Rogers, 2008;Rogers, Sewell, Martin, & Vitacco, 2003), including chronic pain (Aguerrevere, Greve, Bianchini, & Meyers, 2008;Greve et al, 2009;Huss, 2009;Meyers, Millis, & Volkert, 2002).…”
mentioning
confidence: 99%